Competence for Transfection in Staphylococcus aureus - Sjöström, Jan-Eric (1973)
Lysogenicity with phage P11 is a requirement for competence in the presence of calcium ions in Staphylococcus aureus 8325N. The wild-type strain 8325N, lysogenic for the phages P11, P12, and P13, is also competent, but strain 8325-4, a nonlysogenic derivative of strain 8325N, as well as strains 8325-4 (P12) and 8325-4 (P13) could not develop competence. Preincubation of strain 8325-4 with culture filtrates from a competent strain can induce competence, but rabbit anti-P11 serum can neutralize the competence factor. Superinfection of competent strain 8325-4 (P11) with phage P11 at high multiplicities increases the transfection frequency. Uptake of deoxyribonucleic acid by competent cells is dependent on calcium ion concentration, pH, and temperature. Inhibition of energy metabolism or protein synthesis before and during incubation with deoxyribonucleic acid affects the binding and uptake. The ability to develop competence during bacterial growth differs between the wild-type strain (8325N) and a nuclease-deficient mutant (8325N nuc). The wild-type strain has a narrow competence maximum in the early exponential growth phase where no extracellular nuclease activity is produced. The nuc strain shows in addition competence maxima later in the exponential growth phase.